Estimation of Superoxide Dismutase, Matrix-metalloprotinase-9, and Interleukin -18 in Patients with Type Two Diabetes Mellitus - Shatha R. Moustafa; Shawn A. Omar (College of Pharmacy University of Baghdad, 2017)
Antioxidant status imbalance and inflammatory process are cooperative events involved in type 2 diabetes mellitus. This study aimed to investigate     superoxide dismutase as a potential biomarkers of antioxidant imbalance, matrix-metaloprotinase-9,   and interleukin -18  as biomarkers of inflammation in serum and to estimate  the effects of other confounding factors  gender, age and finally measuring the relation among the interested biomarkers. This case - control study included 50 patients,   and   45 of  healthy subjects matched age -gender were also enrolled  in this study as a control group.    The   focused   parameters    were        measured   using      ELISA technique. There was  significant   reduction   in   the   serum   superoxide dismutase level and significant elevation in serum matrix- metaloptotinase-9 and interleukin -18 levels which have been   associated with diabetes.  This finding may explain the role of the defect in antioxidants status   leading to significant reduction in serum superoxide  dismutase  levels  associated with increased inflammatory process leading to significant elevations of a  matrix- metaloptotinase-9 and interleukin -18. These parameters  added a diagnostic information  and evaluated as potential tools for disease risk prediction.  Keywords: Type 2 diabetes mellitus, Superoxide dismutase,   Matrix metaloptotinase-9 and Interleukin -18.